Sex Differences and Cognitive Maps: Studies in the Lab don’t Always Reflect Cognitive Map Accuracy in Everyday Life - Cocquyt, Chantelle M.; Youngson, Nicole; Sutton, Jennifer E. (Frontiers in Virtual Reality, 2022)
The ability to create an accurate mental survey representation, or cognitive map, when moving through an environment varies widely across individuals, and we are still trying to understand the origins of these individual differences. Non-immersive virtual environments used to test for cognitive map accuracy in the laboratory have shown sex differences with a performance advantage for men in some studies but not others. When sex differences are demonstrated, it is unclear whether women’s performance generalizes to familiar and unfamiliar real-world environments. In Experiment 1, 98 participants explored the virtual environment Silcton and afterwards estimated directions between the landmarks in Silcton and arranged landmarks found in Silcton on a map. In addition, they reported frequently visited real-world locations and then estimated directions between them and drew a map of the locations. Men were more accurate on tests of Silcton than women were, although there was no difference between sexes for accuracy with real-world locations. Within sexes, women were more accurate with the real-world locations than Silcton, while men showed the opposite pattern. In Experiment 2, 21 women were tested with Silcton and their familiar real-world locations as in Experiment 1 but were also walked through an unfamiliar real-world area on campus and completed direction estimation and map drawing tests for the new environment. Overall, women were more accurate with the two real-world environments than Silcton, with some evidence that accuracy with the new real-world environment was more accurate than the familiar real-world locations. Overall, women’s ability to create a cognitive map of a virtual environment in the laboratory does not seem to be indicative of their ability to do the same in the real world, and care should be taken when generalizing lab results with virtual environments.